Does fat suppression via chemically selective saturation affect R2*‐MRI for transfusional iron overload assessment? A clinical evaluation at 1.5T and 3T. Issue 2 (26th August 2015) - Krafft, Axel J.; Loeffler, Ralf B.; Song, Ruitian; Bian, Xiao; McCarville, M. Beth; Hankins, Jane S.; Hillenbrand, Claudia M.
Abstract : Purpose: Fat suppression (FS) via chemically selective saturation (CHESS) eliminates fat–water oscillations in multiecho gradient echo (mGRE) R2*‐MRI. However, for increasing R2* values as seen with increasing liver iron content (LIC), the water signal spectrally overlaps with the CHESS band, which may alter R2*. We investigated the effect of CHESS on R2* and developed a heuristic correction for the observed CHESS‐induced R2* changes. Methods: Eighty patients [female, n = 49; male, n = 31; mean age (± standard deviation), 18.3 ± 11.7 y] with iron overload were scanned with a non‐FS and a CHESS‐FS mGRE sequence at 1.5T and 3T. Mean liver R2* values were evaluated using three published fitting approaches. Measured and model‐corrected R2* values were compared and statistically analyzed. Results: At 1.5T, CHESS led to a systematic R2* reduction ( P < 0.001 for all fitting algorithms) especially toward higher R2*. Our model described the observed changes well and reduced the CHESS‐induced R2* bias after correction (linear regression slopes: 1.032/0.927/0.981). No CHESS‐induced R2* reductions were found at 3T. Conclusion: The CHESS‐induced R2* bias at 1.5T needs to be considered when applying R2*‐LIC biopsy calibrations for clinical LIC assessment, which were established without FS at 1.5T. The proposed model corrects the R2* bias and could therefore improve clinical iron overload assessment based on linear R2*‐LIC calibrations. Magn Reson Med 76:591–601, 2016. © 2015 Wiley Periodicals, Inc.